2019
DOI: 10.3892/wasj.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA mismatch repair genes in lung and head and neck cancer (Review)

Abstract: The role of the DNA repair mechanism is to protect genetic material from destabilization. A defect in the DNA mismatch repair (MMR) mechanism has been associated with both hereditary and sporadic tumors. The dysregulation of MMR gene expression has been reported in lung, and in head and neck sporadic tumors. However, the mechanisms through which defects in the DNA MMR mechanism promote lung, and head and neck cancer remain unclear. Environmental factors and epigenetic alterations can significantly alter the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 107 publications
2
7
1
Order By: Relevance
“…Here, our novel findings have shown that the NNK-induced upregulation of "oncomir" miR-21 directly affects MSH2 protein levels in both lung and head and neck squamous cancer cells, and that its inhibition can restore the MSH2 expression phenotype ( Figure 8B). These findings document the regulatory role of miR-21 in the MMR mechanism by directly affecting MSH2, which is a key component of the MutSa complex that recognizes base-base mismatches and short insertion and deletion loops [24]. We also showed that inhibition of miR-21 significantly decreases NNK-induced cell survival.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Here, our novel findings have shown that the NNK-induced upregulation of "oncomir" miR-21 directly affects MSH2 protein levels in both lung and head and neck squamous cancer cells, and that its inhibition can restore the MSH2 expression phenotype ( Figure 8B). These findings document the regulatory role of miR-21 in the MMR mechanism by directly affecting MSH2, which is a key component of the MutSa complex that recognizes base-base mismatches and short insertion and deletion loops [24]. We also showed that inhibition of miR-21 significantly decreases NNK-induced cell survival.…”
Section: Discussionsupporting
confidence: 76%
“…Although multiple diagnostic and prognostic markers have been identified for both lung and head and neck cancers [18,19], the precise molecular mechanisms involved in the development and progression of these malignancies remain unclear.We understand that a functional DNA repair mechanism that includes the recognition and repair of mismatch DNA errors during DNA replication is essential in eliminating the harmful effect of several environmental risk factors, such as NNK, on the exposed cells [20][21][22][23]. A number of studies have shown that reduced expression of mismatch DNA repair (MMR) genes increases the incidence of microsatellite instability [24][25][26][27], which is often found in head and neck cancer [28][29][30][31]. Other studies have also shown that reduced expression of MSH2 or MLH1 genes at the protein or mRNA levels is associated with poor survival and MSI in lung cancer [32][33][34].In addition, MMR deficiency appears to affect the effectiveness of chemotherapy in these cancers [34,35].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the lung lobes with lesions were identi ed using CT beforehand, the tissues to be used for RNA sequencing were selected, resulting in a more robust and direct gene association with the lung lesions. It has been reported that dysregulation of DNA repair and RNA splicing can cause various genetic disorders and eventually lead to cancer [28][29][30]. Taken together, our results demonstrate that genetic alterations due to PHMG exposure may provoke pulmonary in ammation and pulmonary brosis by attenuating the normal recovery mechanism of the lung, consequently resulting in tumorigenesis.…”
Section: Discussionsupporting
confidence: 55%